Road Pavement Condition Survey Study Using Smartphone Application Polycam – Lidar Parameter Surface Distress Index (SDI) - Siregar, Amiruddin; Wiyono, Sugeng; Kausarian, Husnul; Elizar, Elizar (Jurnal Ilmu Dan Rekayasa Sipil, 2024)
Road damage in various regions is a complex problem, especially for road users, such as long travel times, congestion, traffic accidents, and others. In realizing good road services, the government issued Ministerial Regulation No. 11 / PRT / M / 2011 concerning road database management, including cross-section and longitudinal road inventory surveys. Technological developments are increasingly sophisticated and can be used to survey road damage conditions. The purpose of this study was to analyze road pavement conditions with the help of the Polycom-Lidar Smartphone Application based on the Surface Distress Index (SDI) method. The method used in this study is a direct survey using manual equipment and collecting road damage data using a smartphone model iPhone 13 Pro max Version iOS 16.3.1 serial number CG2WGPQKH5 IMEI 35 478625 594256 3 and the Polycom LIDAR application. The results obtained that the road pavement condition survey with the smartphone polycam lidar application can be used with more selective results to detect wheel rut damage (rutting) and more guaranteed data because 3D analysis can be done repeatedly without re-surveying the field. Of the 15 segments reviewed, the SDI value has 1 different segment, namely in Segment I station 0 + 600 -0 + 800. The influencing factors are accuracy, and skill in analyzing scan results, especially when digitizing damage dimensions on Polycom lidar scan results. The type of handling does not differ because the difference in SDI numbers is small so it does not describe a significant difference in road conditions.